Triglycerides of Crude Palm Oil to Biokerosene: Studies on Electrolysis and Electromagnetic Effect - Sri Rizki Putri Primandari; Krismadinata Krismadinata; Dori Yuvenda; Remon Lapisa; Andre Kurniawan; Mulianti Mulianti; Muhammad Djoni Bustan; Sri Haryati; Gusni Sushanti; Tarig Elshaarani; Yus Donald Chaniago (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
Crude Palm Oil (CPO) is a potential feedstock for biokerosene. However, it is problematic when used directly because it is gummy, has a high viscosity and is degradable. Various conversion processes have been conducted that directly convert CPO into biokerosene, but it requires high temperature and pressure. Therefore, as a novelty, this study aims to develop the technology for converting triglycerides into biokerosene under relatively low operating conditions and producing similar petroleum kerosene by electrolysis-assisted and electromagnetic induction. In this study, the conversion technology process was conducted in three steps (i) converting triglycerides to Free Fatty Acids (FFA), (ii) converting FFA to alkanes, and (iii) converting alkanes to biokerosene. Step (ii) is assisted by the electrolysis process, meanwhile, step (iii) is assisted by electromagnetic irradiation. The finding showed that electrolysis obtained 73.47% yield of alkanes and electromagnetic irradiation obtained 78.02% yield of biokerosene. Biokerosene is almost close to kerosene-based petroleum in terms of colour Saybolt, flash point and Net Heating Value. The findings of this study may provide an alternate technology approach for biokerosene synthesis and solution kerosene scarcity.